Six-minute Walk Test in Children with Cerebral Palsy: Comparing the Walking Distance between Different Level of Communication Function - Budiati Laksmitasari; Luh Karunia Wahyuni; Tirza Z Tamin (Indonesian Journal of Physical Medicine & Rehabilitation, 2018)
Introduction: Children with cerebral palsy (CP), six-minute walk test (6MWT) is more difficult to perform because some children have communication impairment. The objective to study the distance of 6MWT among different level of communication in children with CP.Methods: This study was cross-sectional study , in a Rehabilitation Clinic, on Juli to December 2018. The subjects were children aged 7-18 years old with cerebral palsy with Gross Motor Function Classification System (GMFCS) I-III, Communication Function Classification System (CFCS) I-III, able to walkindependently with or without aid, and understand the instruction of 6MWT. All the subjects performed 6MWT. Level of communication function was evaluated by CFCS. The 6MWD between CFCS groups were compared.Results: There were 23 subjects mean aged 9 years old, consisted of 17(73.9%) male and 6(26.1%) female, with GMFCS level I-III in sequence were 3(13%), 11(47.8%), and 9(39.1%), also with CFCS level I-III in sequence were 5(21.7%), 7(30.4%), and 11(47.8%). Subjects with verbal communicationwere 14(60.9%) and nonverbal communication were 9(39.1%). The median of 6MWD in group with CFCS level I, II, and III respectively were 115 (60-282), 161 (17.5-281), and 135 (23-280) m. There was no significant difference in 6MWD between different groups of CFCS (p=0.960).Conclusion: There were no difference in walking distance on 6MWT among different level of communication function in children with CP.Keywords: Cerebral palsy, Six-minute walk-test, Six-minute walking-distance, Communication Function Classification System (CFCS)